2014
DOI: 10.1007/s11240-014-0690-2
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene selection in Artemisia annua L., a plant species producing anti-malarial artemisinin

Abstract: The selection and validation of reference genes are essential for gene expression studies by real-time quantitative PCR. The genetic map of Artemisia annua L., a Chinese medicinal plant species producing anti-malarial artemisinin, has been reported. However, few reference genes of A. annua have been estimated for real-time quantitative PCR until now. In this study, ten putative housekeeping genes, including ACT, UBQ, TUB, 18S rRNA, EF1a, CYP, RPL13D, TUA, RPII and GAPDH, were chosen for identifying expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…In the current study, the RefFinder analysis, identified MUB as the most stable gene in the all-samples set. Meanwhile, UBC , α - TUB and β - TUB had relatively poor expression stability values, which is similar to previous results in Artemisia annua L [ 29 ] and Brassica napus [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, the RefFinder analysis, identified MUB as the most stable gene in the all-samples set. Meanwhile, UBC , α - TUB and β - TUB had relatively poor expression stability values, which is similar to previous results in Artemisia annua L [ 29 ] and Brassica napus [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, it is essential to systematically evaluate potential reference genes to ensure that they are appropriate for a specific experimental condition [ 23 ]. To date, IGG ( http://icg.big.ac.cn ), a wiki-driven knowledgebase that collects internal reference genes for diverse species, has been integrating a comprehensive collection of more than 150 plants [ 24 ], such as Arabidopsis [ 25 ], cucumber [ 26 ], wheat [ 27 ], rice [ 28 ], Artemisia annua [ 29 ], and Panax ginseng [ 30 ]. However, it has not been used for the systematic selection of a reference gene for qRT-PCR analysis in I. indigotica under hormone treatment or low-nitrogen stress, a factor that impedes functional gene studies.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative PCR (qPCR) was performed on an iQTM5 Multicolor Real‐Time PCR Detection System (Bio‐Rad, USA) in 96‐well plates using GoTaq® qPCR Master Mix (Promega) according to the protocol. The internal control genes corresponded to actin and EF1ɑ, which were previously reported to be stable reference genes under low temperature stress . The specific primers for target genes are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…The upper part of the figure displays the respiratory chain complexes and the lower portion represents their subunits as rectangles (red ones are the transcripts unique to control sample when compared to stress the bottom part, rectangles indicate the subunits of each respiratory chain complex. Red colored boxes represent the genes that were present exclusively in control sample whereas green boxes represent the genes present in reference organism 65 68 . …”
Section: Resultsmentioning
confidence: 99%